2020
DOI: 10.3390/biom10060813
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Euterpe oleracea Mart. As a New Perspective for Disease Treatment and Prevention

Abstract: Euterpe oleracea Mart. (EO), popularly known as açaí, belongs to the Arecaceae family and grows abundantly in Brazil. The fruit of this palm tree is widely used because of its anti-inflammatory and antioxidant properties. In this review, a search for literature and patent technological prospecting has been performed on the use of EO to treat and prevent diseases as well as to prepare pharmaceutical formulations. EO leaves, fruits, and oil stand out for their large number of pharmacological activities such as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 97 publications
0
28
0
Order By: Relevance
“…Euterpe oleracea Mart. from Arecaceae grows in many countries of South America (i.e., Brazil, Ecuador, and Venezuela) and is a source of nutritious fruits (acai berry), leaves, and seeds [98][99][100]. Phytochemical studies showed that extract from seeds of E. oleracea contain polyphenolic compounds, for example, proanthocyanidins, epicatechin, catechin [101].…”
Section: Plant Extracts In Animal Models Of Preeclampsiamentioning
confidence: 99%
See 2 more Smart Citations
“…Euterpe oleracea Mart. from Arecaceae grows in many countries of South America (i.e., Brazil, Ecuador, and Venezuela) and is a source of nutritious fruits (acai berry), leaves, and seeds [98][99][100]. Phytochemical studies showed that extract from seeds of E. oleracea contain polyphenolic compounds, for example, proanthocyanidins, epicatechin, catechin [101].…”
Section: Plant Extracts In Animal Models Of Preeclampsiamentioning
confidence: 99%
“…Phytochemical studies showed that extract from seeds of E. oleracea contain polyphenolic compounds, for example, proanthocyanidins, epicatechin, catechin [101]. Extracts from fruits include quercetin, catechin, procyanidin oligomers, and phenolic acids (ferulic acid, vanillic acid, syringic acid) [100]. Various preparations from different parts of this plant exert a wide range of pharmacological activities, mainly tissue-protective, antioxidative, anti-inflammatory, anti-hyperlipidemic, and anti-hypertensive effects [99,100].…”
Section: Plant Extracts In Animal Models Of Preeclampsiamentioning
confidence: 99%
See 1 more Smart Citation
“…The açaí fruit, a small and round dark purple berry, gained a great commercial interest in the past years due to its nutritional and functional properties. According to in vitro and in vivo studies, it has been associated with relevant biological activities such as antioxidant and anti-inflammatory properties, as well as anti-carcinogenic, antimicrobial, anti-diabetic, anti-neurodegenerative, and cardio-protective effects [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In their review, de Almeida Magalhães et al performed a search for literature and technological patents aiming to treat and prevent diseases, as well as to prepare pharmaceutical formulations, suggesting a growing interest in Euterpe oleracea Mart. (EO) leaves, fruits and oil, with a set of actions pointing to the development of promising new drugs for clinical use, although more studies should be done to consolidate initial results [ 20 ]. Gall et al revealed the effect of long-term cannabidiol (CBD) treatment on the chronic unpredictable mild stress (CUMS) model of depression.…”
mentioning
confidence: 99%